The Medium may be the Same but the Message is Different: Comparing the Tweets of U.S. Presidents Obama and Trump - Whissell, Cynthia (Advances in Social Sciences Research Journal, 2018)
Monthly averages for Tweets posted by Obama in 2015-16 and Trump in 2017 were compared in terms of their frequency of occurrence, their tendency to be replies or retweets, the emotionality of their language, and their vocabulary. There were extreme differences in frequency of tweeting (r2=.88, p<.001), with Trump tweeting more frequently. There were also considerable differences in Pleasantness of Tweet language, with Obama employing more Pleasant words (r2=.31, p<.001). Trump retweeted proportionally more often while Obama replied proportionally more often (r2=.28, .20, p<.05). Additionally, each president employed a distinct vocabulary. Obama employed first person plural pronouns (“we”, “us”) more often (r2=.43, p<.001). It was possible to predict president of origin with extremely high success (97% or better) whether frequency of tweeting was included in the predictive scheme or not. While the medium the two presidents were employing was the same, their resulting messages were very different.